Moral challenges of Modern Lifestyle for Youth and Their Solutions in the Light of Islamic Teachings - Aasia Rasheed; Ume Farva (Pakistan Journal of Islamic Research)
Whenever something goes morally wrong with the children or youth, even though they are not our own children, still we are responsible for that. Why? because we are Muslims and belong to a religion which teaches us to be moral human being and try to make a human moral influence on others in society. This article is an attempt to highlight the moral challenges faced by the Muslim youth living an environment where access of evil and evildoing is given in so much attractive way to avoid them is hardly possible. Due to the absence of Islamic values from the governing system of today’s society Muslim youth, whether they are in the Islamic world or studying in the West, are morally and socially facing different challenges both at individual and social level. Through the discussion and description presented in this paper, importance of Islamic values and teachings in the governing system of society has been highlighted. First part of the paper gives concept of youth in Islamic teachings. Second part provides description of factors affecting the moral behavior of Muslim youth. In third part some solutions have been given in the light of teachings of Islam that how to address moral issues raised by modern trends. In the last part summary of the article has been given in the form of conclusion. Islamic religiosity as tool of life satisfaction, facilitate the youth in more positive way. Based upon descriptive and analytical study of the available research discussion of the paper will examine the relationship between Islamic system of religiosity to address the issues and challenges of deviant behavior of Muslim youth affected by modern life style. Based on a critical review of the current primary literature about the issues and challenges of modern advancements and their effects on Muslim youth, the paper proposes a more broadly applicable definition of Islamic religiosity and its model of life satisfaction at both individual and social level.